Representing african music: Postcolonial notes, queries, positions - Agawu, Kofi (New York Routledge, 2003)
The aim of this book is to stimulate debate by offering a critique of discourse about African music. Who writes about African music, how, and why? What assumptions and prejudices influence the presentation of ethnographic data? Even the term "African music" suggests there is an agreed-upon meaning, but African music signifies differently to different people. This book also poses the question then, "What is African music?" Agawu offers a new and provocative look at the history of African music scholarship that will resonate with students of ethnomusicology and post-colonial studies. He offers an alternative "Afro-centric" means of understanding African music, and in doing so, illuminates a different mode of creativity beyond the usual provenance of Western criticism. This book will undoubtedly inspire heated debate--and new thinking--among musicologists, cultural theorists, and post-colonial thinkers. Also includes 15 musical examples